Reforming Intergovernmental Fiscal Relations in Argentina - Cuevas, Alfredo (IMF Working Papers; Working Paper ;, 2003)
Argentina has committed itself to a reform of its revenue-sharing system. This paper examines this system and the issues involved in its redesign, and discusses the pros and cons of various options with a view to specifying a preferred approach.